(untitled) (Agricultural Engineering, 2016)
The objective of the paper was to analyse possibilities and advantages of energy recovery from municipal solid waste during the thermal treatment in boilers with a moving grate system. The state of the art of Waste-to-Energy (WtE) boilers was investigated mainly by reviewing papers published in scientific journals and at conferences but also by taking into consideration reports from research institutes. The article shows the main aspects that determine the popularity of this type of boilers as well as new solutions which greatly improve the process of thermal treatment of waste. It proves that waste incineration boilers based on the moving grate technology prevail mainly because of its simplicity, reliability and effective energy generation to which special attention was paid. Additionally, the article mentions how WtE boilers are designed and operated to incinerate municipal waste with a great variation in composition with simultaneous notable energy recovery and low environmental impacts. Contemporary development of the Polish WtE infrastructure can be a very important factor influencing the national municipal waste management together with renewable energy and energy efficiency policies.